Relationship between Serum Vitamin D Status and Gestational Diabetes Mellitus - Bushra Jabbar Hamarashid1 , Atiya Kareem Mohammed 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background The association between vitamin D deficiency and risk of gestational diabetes mellitus(GDM) are proposed by several studies. Gestational diabetes mellitus complicates nearly 1% to 28% of allpregnancies and had an adverse effect for both mother and offspring. Vitamin D deficiency is one of themodified risk factors that can be corrected in the pre-conceptional period.Objectives The current study aims to investigate and compare the serum levels of 25-hydroxyvitamin D3 inpregnant women with GDM and non-GDM control subjects.Methods In a descriptive study plasma 25-hydroxyvitamin D was assessed in a 100 women with GDM andit was compared to 162 non-GDM at gestational age above 24 weeks that was conducted in the MaternityTeaching Hospital in Sulaimani city from December 2018 to January 2019. The study used face-to-faceinterviews to collect the data through a specific written questionnaire. At the same time serum vitamin Dstate was examined using the Roche Elecsys vitamin D3 assay.Results There were no statistical significant differences found between two groups of GDM and nonGDM. The result of the study showed that the prevalence of vitamin D deficiency higher in the GDM group(77.0%) compares to non-GDM group (68.5%). The study found that socioeconomic state (p-value=0.069),body mass index(p-value=0.038), education (p-value=0.000), residency (p-value=0.000), age at marriage(p-value=0.023), gravida (p-value=0.014), and para (p-value=0.001), was significantly different betweentwo groups of GDM and non-GDM.Conclusion Overall, results imply that the vitamin D deficiency more prevalent among GDM group compareto non-GDM group, but the differences was not statically significant.